Case Report of Percutaneous Retrograde Transcollateral Recanalization of the Superior Mesenteric Artery via the Celiac Artery for Acute Mesenteric Ischemia. Issue 50 (December 2015) - Gupta, Prateek K.; Smith, Brigitte K.; Yamanouchi, Dai
Abstract : Abstract: Revascularization for acute mesenteric ischemia (AMI) can be achieved through a bypass from the aorta or iliac arteries, embolectomy, open exposure of SMA and retrograde recanalization and stent, or percutaneous antegrade stenting. Flush occlusion of the SMA can make antegrade recanalization very challenging and is usually unsuccessful. We present a novel approach for recanalization of superior mesenteric artery (SMA) via the celiac artery for acute mesenteric ischemia. A 69-year-old lady with previous endarterectomy of SMA and extensive small bowel resection presented with severe abdominal pain, emesis, leukocytosis, and imaging finding of new SMA flush occlusion. She refused to consent for a laparotomy. Percutaneous retrograde transcollateral recanalization of SMA was performed via the celiac artery through the pancreaticoduodenal arcade, and the SMA then stented. This resulted in subsequent resolution of patient's symptoms and discharge. SMA revascularization with retrograde transcollateral wiring technique is an important tool in the armamentarium of the vascular care specialist when antegrade percutaneous approach and open exposure via laparotomy are not an option.